On computing the irregularity of R-corona product types of graphs - Berberler, Zeynep Nihan (Utilitas Mathematica, 2019)
The imbalance of an edge uv in a graph G is defined as \d(u)- d(v)|, where d(u) denotes the degree of u. The irregularity of G, denoted irr(G), is the sum of the edge imbalances taken over all edges in G. In this paper, we focus our investigation to the study of how the irregularity of a graph changes with operations based on R -graphs. Furthermore, we find exact formulae for the irregularity of a class of composite graphs, namely, R -corona products. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.